Regulatory role of the endocannabinoid system on glial cells toward cognitive function in Alzheimer’s disease: A systematic review and meta-analysis of animal studies - Kamaruzzaman, Mohd Amir; Romli, Muhammad Hibatullah; Abas, Razif; Vidyadaran, Sharmili; Hidayat Baharuldin, Mohamad Taufik; Nasaruddin, Muhammad Luqman; Thirupathirao, Vishnumukkala; Sura, Sreenivasulu; Warsito, Kabul; Mohd Nor, Nurul Huda; Azwaruddin, Muhammad Amsyar; Alshawsh, Mohammed Abdullah; et al. (Frontiers in Pharmacology, 2023)
The purpose of this systematic review gain a conclusive properties of endocannabinoid towards cognition in animal studies by looking at the mechanism modulated on glial cells. Six database were searched encompassing including EBSCOHost, Scopus, PubMed, CINAHL, Cochrane, and Web of Science. Twenty-six studies were identified to be fit into inclusion criteria. Once obtained the included studies were assessed for the quality using SYRCLE's risk of bias tool. We can conclude that glial cell modulated by endocannabinoid promotes cognitive improvement in Alzheimer's disease like animal model.